143 Development and clinical application of a tool to identify frailty in elderly patients with gynecological cancers. (13th November 2020) - Ferrero, A; Villa, M; Attianese, D; Coppo, M; Borghese, M; Badellino, E; Fuso, L; Biglia, N
Abstract : Objectives: Aim of this prospective study is the development and clinical application of a tool to identify frailty in patients > 70 years old affected by either ovarian or endometrial cancer. After identifying a cut off to establish frailty, differences in terms of surgical complications and chemotherapy toxicities were verified. Methods: The test consists of 20 items combining comorbidities and functional aspects. At the onset or at the first recurrence 52 patients were evaluated before treatment's administration. Results: Considering 'completion of treatment' as parameter to discriminate frail patients, a cut off > 4 resulted the best in terms of specificity and sensibility (Sp 100%, Sn 77, 6%) to identify frail group. 36% of patients resulted frail. Frailty was associated with longer hospitalization after surgery (11, 5 days vs 8, 3 days, p = 0, 01). No differences occurred in the incidence of post-operative adverse events, but grade III and IV complications were observed exclusively in 2 frail women. Only 38, 5% of frail patients completed chemotherapy treatment; delay in chemotherapy administration has been reported in 77% of frail patients (vs 17, 6% in 'fit group', p = 0, 008) and dose reduction in 70, 6%. Thrombocytopenia (69.3% vs 0%, p = 0, 002) and anemia (77% vs 29.4%, p = 0, 002) were more prevalent in the frail group, as well as non-hematological adverse events. Conclusions: Our tool seems to effectively stratify elderly patients with gynecological cancers according to frailty, in order to choose the best treatment for frail women and avoid undertreatment in fit ones.